Interpreting Mafqūd in Modern Courts: The Influence of Classical Fiqh Schools on Judicial Ijtihad in Indonesia - Hamda Sulfinadia; Jurna Petri Roszi; Amirulhakim Amirulhakim; Syahrul Anwar (Justicia Islamica, 2026)
This article addresses the question of how inheritance cases involving mafqūd are resolved in Indonesian Religious Courts and to what extent judicial reasoning reflects madhhab moderation within Islamic law. The issue of mafqūd, defined as a missing person whose life or death is legally uncertain, has long generated juristic debate due to divergent interpretations of the principle of istishḥāb al-ḥāl and the scope of judicial authority in determining death. This study positions itself within normative Islamic legal scholarship by examining judicial practice as an arena where classical fiqh interacts with contemporary positive law. Using a qualitative legal method, the research analyses twelve purposively selected Religious Court decisions through document study and juridical analysis. Operationally, the rulings are examined by comparing judges’ legal reasoning with doctrines from the Ḥanafī, Mālikī, Shāfiʿī, and Ḥanbalī schools, as well as with the Compilation of Islamic Law. The findings reveal that judges do not strictly adhere to a single madhhab, but instead employ ijtihād qaḍāʾī to selectively integrate classical opinions with statutory norms to ensure legal certainty and substantive justice. This judicial pattern demonstrates madhhab moderation as a methodological approach rather than doctrinal compromise, contributing, theoretically, to the concept of living fiqh and, practically, to fair inheritance adjudication in Religious Courts.